Performance in Construction, The Influence of Middle Management on the Construction Workers’ Performance in Production - POSTMA, THOMAS (My University, 2016)
A lack of human focus in construction and site management and an increasing internationalisation has been identified in the literature. The research aim of the thesis is to study the performance of the construction industry, to find out where and how the industry can improve itself on construction management during production. Several performance indicators were identified and studied, based on the ‘Transaction Cost Economics’ (TCE) and the ‘Resource Based Theory’ (RBT). A human focus is chosen in this study and the scope is given with the execution phase of construction projects. The analysis revealed that the interviewed managers identified areas, which they are not satisfied with. Four performance indicators and three organizational support performance indicators were selected for the discussion. In order to improve the construction sector, it was found that in some cases, the efficiency of time, cost and quality management, and project leadership could be improved. The performance indicators of HRM, training and knowledge management have areas which are not paid enough attention to and should therefore improve.
Keywords: Samhällsbyggnadsteknik; Civil Engineering